Investigation of relationship between coefficients of operation efficiency of diesel particulate matter filters of diesel ICE. Part 1: Particulate matter emission and opacity - Kondratenko, O. M. (NTU "KhPI", 2018)
This article describes the results of analysis and numerical study of prof. I.V. Parsadanov conversion formula as the one of relevant issues of the metrological features of determination of PM mass hourly emission of piston ICE on the testing bench without dilution tunnel. Purpose of the study is detection of relationship between magnitudes of cleaning efficiency coefficients of particulate matter filter of diesel piston ICE for opacity and emission of particulate matters with using of conversion formula for whole diapason of changing of influencing factors. It was showed that the magnitudes of values of efficiency coefficients of operation of particulate matter filter of diesel internal combustion engine for indicators of opacity and concentration of unburned hydrocarbons in exhaust gas which was obtained by direct measurements during bench motor tests and also mass hourly emission of particulate matter in exhaust gas flow which was obtained with using of the conversion formula, is not equal to each other for every individual operational regime of diesel engine. Calculation assessment and graphical illustration of relationship between magnitudes of this coefficients for opacity and emission of particulate matter for whole diapason of changing of influencing factors was carried out.

Проаналізовано і розрахунково досліджено формулу перерахунку проф. І.В. Парсаданова як одного з актуальних питань метрологічних особливостей процесу отримання значень масового годинного викиду твердих частинок поршневого ДВЗ на моторному випробувальному стенду, не обладнаному тунелем розведення. Метою дослідження є виявлення співвідношення значень коефіцієнтів ефективності роботи фільтра твердих частинок дизельного поршневого ДВЗ за викидами твердих частинок та димністю відпрацьованих газів із застосуванням формули перерахунку для всього діапазону зміни значень впливаючих факторів. Показано, що значення коефіцієнтів ефективності роботи фільтра твердих частинок дизельного двигуна внутрішнього згоряння за показниками димності й концентрації незгорілих вуглеводнів у відпрацьованих газах, отримані прямими вимірюваннями у ході стендових моторних випробувань, а також масового годинного викиду твердих частинок з потоком відпрацьованих газів, отримані за вказаною формулою перерахунку, не збігаються для кожного стаціонарного режиму його роботи. Розрахунково оцінено та проілюстровано графічно співвідношення значень цих коефіцієнтів за димністю і викидом твердих частинок для всього діапазону зміни впливаючих факторів.
Дослідження співвідношення коефіцієнтів ефективності роботи фільтра твердих частинок дизельного ДВЗ. Частина 1: Викид твердих частинок і димність